1996
DOI: 10.1108/00438029610115479
|View full text |Cite
|
Sign up to set email alerts
|

TQM in the service sector

Abstract: Underlines the dominance of the service sector in the future global economy and explains the characteristic features and elements of a service organization. Explains that with the growing maturity of society with respect to education, culture and standards of living, the user expectations and demands for improved quality of service are increasing. This is part of the pressure causing service organizations to explore total quality management (TQM) as a means of driving quality improvement into all their activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 4 publications
0
34
0
3
Order By: Relevance
“…Although, in principle, this aspect should be considered during this transition. This concept will be incorporated in the lepton-pair interferometry and work in this line is in progress [38]. It is also straight forward to extend this analysis to LHC energies.…”
Section: Discussionmentioning
confidence: 99%
“…Although, in principle, this aspect should be considered during this transition. This concept will be incorporated in the lepton-pair interferometry and work in this line is in progress [38]. It is also straight forward to extend this analysis to LHC energies.…”
Section: Discussionmentioning
confidence: 99%
“…Levitt (1981) suggested that the universal conceptualisation of the service quality construct may be futile, while others argue that service quality is either industry or context specific (Cronbach 1986, Babakus andBoller 1992). Despite the fact that service quality is not synonymous with customer service, Mohanty and Behara (1996) argued that customer service and customer relations are part of service quality. We observe that there is no clear-cut postulated theory for service quality, customer satisfaction and patronage intention; however, viewing customers as the future assets of the organisation (Mohanty and Yadav 1994) following four types of linkages ( Figure 2) can be visualized when the service provider is entirely represented by service quality , Prakash et al 2011b).…”
Section: Linkages Of Service Qualitymentioning
confidence: 94%
“…TQM is not a destination, but a journey towards improvement of the process Hunt (1991). According to Mohanty and Lekhi (2002) [11] TQM is a programmatic long-term systems approach initiated and driven by the top management to bring about a total culture change to meet the dynamic needs of the customer and create a loyal and diversified customer base. According to Kanji et al (1999) [9] TQM is a process of continuously satisfying customer requirements at the lowest possible cost by harnessing the capabilities of everyone.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kotler (1993) defines services as any kind of performance that one party can offer to another that is essentially intangible and does not results in the ownership of anything. As observed by Mohanty and Lekhi (2002) [11] there are four important characteristics of services i.e., intangibility, perishability, inseparability and heterogeneity. On the whole service sector integrates all the above components, involving a large number of staffs working with a definite purpose to satisfy different needs of the customers.…”
Section: Tqm In Service Sectormentioning
confidence: 99%